TEUMAKASIH BUKAN SEKADAR KATA: FILOSOFI UNGKAPAN ACEH SEBAGAI RESISTENSI BUDAYA GLOBAL - Muhammad Raihan (NIHAYAH: Journal of Islamic Studies, 2025)
The extinction of local languages has become a pressing global issue, as highlighted by UNESCO's alarming statistic that one regional language disappears every two weeks. Amid the tide of global linguistic homogenization, the Acehnese term teumakasih emerges as a subtle yet potent symbol of cultural resistance. This study aims to explore the revitalization of teumakasih in the context of glocalization, as well as its embedded semantic and identity values. A qualitative approach using linguistic ethnography and semiotic analysis was employed to trace the word’s usage in both physical spaces (coffee shops, prayer houses) and digital platforms (social media, marketplaces). Findings reveal that teumakasih is more than a polite expression; it carries a distinct local philosophy: teuma means "to return" and kasih means "love", forming a notion of sincere and spiritual giving. In glocal spaces such as Acehnese coffee shops in Jakarta and Melbourne, teumakasih is used to signify Acehnese cultural identity. Furthermore, intergenerational transmission through online practices and everyday interactions demonstrates that language functions as a crucial medium for preserving collective memory. Thus, local expressions like teumakasih serve as a final stronghold in the face of global cultural identity crises. This study asserts that language revitalization depends not only on formal policies but also on the lived, everyday practices embedded in simple spoken words.